Responses of Coastal Ecosystems to Climate Change: Insights from Long-Term Ecological Research. (16th August 2022) - Reed, Daniel C; Schmitt, Russell J; Burd, Adrian B; Burkepile, Deron E; Kominoski, John S; McGlathery, Karen J; Miller, Robert J; Morris, James T; Zinnert, Julie C
Abstract: Coastal ecosystems play a disproportionately large role in society, and climate change is altering their ecological structure and function, as well as their highly valued goods and services. In the present article, we review the results from decade-scale research on coastal ecosystems shaped by foundation species (e.g., coral reefs, kelp forests, coastal marshes, seagrass meadows, mangrove forests, barrier islands) to show how climate change is altering their ecological attributes and services. We demonstrate the value of site-based, long-term studies for quantifying the resilience of coastal systems to climate forcing, identifying thresholds that cause shifts in ecological state, and investigating the capacity of coastal ecosystems to adapt to climate change and the biological mechanisms that underlie it. We draw extensively from research conducted at coastal ecosystems studied by the US Long Term Ecological Research Network, where long-term, spatially extensive observational data are coupled with shorter-term mechanistic studies to understand the ecological consequences of climate change.